Pengaruh Diskon Terhadap Keputusan Pembelian Kosmetik Halal Dengan Minat Beli Sebagai Variabel Intervening - Firza Oktavia; Achmad Fageh (LPPM Universitas BSI, 2022)
The pandemic period demands more selective consumption of goods, including beauty products. Purchases in the cosmetic industry have decreased due to the lack of a marketing strategy that results in purchasing decisions. However, to deal with this, the marketplace is present as a solution in dealing with this decline, so that the marketplace is one of the strategies in combining the entire ecosystem and has the potential to increase sales which makes it easier for consumers to make decisions to buy goods by knowing their products without having to leave the house. However, before making a decision to buy, it is necessary to look at the rules that balance which are seen from the negative and positive sides as the best solution. The purpose of this research is to find out and prove the effect of the discount variable and purchasing decisions on halal cosmetics with the intervening variable of buying interest. The research method uses quantitative methods with descriptive quantitative approaches and research instruments in the form of questionnaires obtained from respondents directly, based on interpreted data collection, the results show that the discount variable has a significant influence on purchasing decisions through buying interest as a mediating variable.Keywords: Discounts, Purchase Interest, PurchaseiDecisions